Pengaruh Kecemasan Menghadapi Pemutusan Hubungan Kerja Terhadap Motivasi Kerja Karyawan Hotel di Kota Padang - Iqbal, Muhammad; Frinaldi, Aldri (Policy, Law and Political Research Center, 2023)
In March 2020, Covid-19 entered Indonesia. The widespread spread of COVID-19 has had an impact on society, the economy and business. Previously, businesses could function independently; Now, to stop the spread of disease, businesses must provide dedicated, adaptable physical environments and allow employees to work from home. Hotels need staff members who perform well in running hotel operations. Human resources (HR) are now viewed by organizations and businesses as important assets, not just as resources in the current era of globalization. The aim of this research is to examine the influence of anxiety due to layoffs on the motivation of hotel employees in Padang City to maintain their jobs. This research uses quantitative methods, a form of research that is included in the descriptive research category. This particular method uses a correlational approach. A simple regression analysis method was used to analyze the research. Based on the research results of the anxiety variable with a t-value of 2.188 and a sig value (0.031 < 0.05) with df = 100-2 = 98, a t table of 1.960 is obtained. From the results above it can be seen that tcount > ttable or 2,188 > 1,960, meaning that Ha is accepted and Ho is rejected. So it can be concluded that anxiety about facing layoffs has a positive and significant effect on the work motivation of hotel employees in Padang City.